Granulocyte-Macrophage Colony-Stimulating Factor Production and Tissue Eosinophilia in Chronic Rhinitis - Peric, Aleksandar; Spadijer-Mirkovic, Cveta; Matkovic-Jozin, Svjetlana; Jovancevic, Ljiljana; Vojvodic, Danilo (International Archives of Otorhinolaryngology, 2016)
Introduction Granulocyte-macrophage colony-stimulating factor (GM-CSF) is a strong proinflammatory cytokine that takes part in allergic nasal inflammation as an eosinophil colony-stimulating factor. However, the role of GM-CSF in non-allergic rhinitis has not been fully explored.Objectives The aim of this investigation was to assess the concentration of GM-CSF in nasal secretions of patients with non-allergic rhinitis with eosinophilia syndrome (NARES) in comparison to patients with perennial allergic rhinitis (PAR) and healthy subjects, as well as to assess the relationship with the degree of eosinophilic inflammation and clinical characteristics of the patients.Methods Fourteen patients with diagnosis of NARES, 14 PAR patients, and 14 healthy subjects were included in this cross-sectional study. All patients underwent symptom score assessment, nasal endoscopy, allergy testing, and cytological evaluation. The concentration of GM-CSF in nasal secretions of all participants was measured by enzyme-linked immunosorbent assay (ELISA).Results We found significantly higher levels of GM-CSF in patients with NARES than in the control group (p = 0.035). The percent of eosinophils in nasal mucosa was higher in NARES patients in comparison to patients with PAR (p < 0.001) and control patients (p < 0.0001). We found positive correlations between GM-CSF levels and eosinophil counts only in NARES patients.Conclusion The concentrations of GM-CSF in nasal secretions correlate well with eosinophil counts in the nasal mucosa of NARES patients. These facts indicate a possible role of GM-CSF as a favorable marker for assessment of nasal disease severity and the degree of chronic eosinophilic inflammation in the nasal mucosa.
Keywords: rhinitis; allergic; perennial; nasal lavage fluid; eosinophilia; cytokines